2019
DOI: 10.1007/s10096-019-03749-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological profile of gastrointestinal tuberculosis: a multinational ID-IRI study

Abstract: Data are relatively scarce on gastro-intestinal tuberculosis (GITB). Most studies are old and from single centers, or did not include immunosuppressed patients. Thus, we aimed to determine the clinical, radiological, and laboratory profiles of GITB. We included adults with proven GITB treated between 2000 and 2018. Patients were enrolled from 21 referral centers in 8 countries (Belgium,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 25 publications
0
37
0
1
Order By: Relevance
“…While the incidence of pulmonary TB is decreasing, the incidence of extra-pulmonary TB is increasing, which may be due to the improvement in life expectancy, increased predominance of females in the population, and the decrease of BCG vaccines worldwide [11]. In the last two decades, the incidence of GI TB, including colonic TB, has been increasing, which may be attributed to the increased incidence of HIV infections and the rising use of immunosuppressive drugs [5]. One study showed that coinfection of TB with HIV can be as high as 73% [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the incidence of pulmonary TB is decreasing, the incidence of extra-pulmonary TB is increasing, which may be due to the improvement in life expectancy, increased predominance of females in the population, and the decrease of BCG vaccines worldwide [11]. In the last two decades, the incidence of GI TB, including colonic TB, has been increasing, which may be attributed to the increased incidence of HIV infections and the rising use of immunosuppressive drugs [5]. One study showed that coinfection of TB with HIV can be as high as 73% [12].…”
Section: Discussionmentioning
confidence: 99%
“…TB most commonly affects the lungs, but can also be extra-pulmonary [2]. Mycobacterium tuberculosis can infect the gastrointestinal (GI) tract, most commonly in the terminal ileum, small intestine, and colon [3][4][5][6][7]. GI TB is the sixth most common site of extra-pulmonary TB, and before the development of antitubercular drugs, autopsies showed that GI tract was involved in more than 90% of the cases [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the stomach accounted for only 6% of cases in one recent multinational study, and oesophageal involvement is limited to case reports and small series. 54 Patients present with abdominal pain that may be of several months' duration, progressive gastric outlet obstruction, a right iliac fossa mass, altered bowel habits, and bleeding. 55 Intestinal tuberculosis responds well to standard antituberculosis therapy, but may result in perforation if left untreated.…”
Section: Mycobacterium Tuberculosismentioning
confidence: 99%
“…M. tuberculosis preferentially affects the ileocaecal region, because of the abundant lymphoid tissue at that site. In contrast, the stomach accounted for only 6% of cases in one recent multinational study, and oesophageal involvement is limited to case reports and small series 54 . Patients present with abdominal pain that may be of several months’ duration, progressive gastric outlet obstruction, a right iliac fossa mass, altered bowel habits, and bleeding 55 .…”
Section: Bacterial Infection Of the Upper Gastrointestinal Tractmentioning
confidence: 99%